The Relationship Between Depressive Symptomatology and Alcohol Consumption in the Latin American Population Based on Gender and Age - Villanueva-Blasco, Víctor José; Espitia-Cepeda, Catalina; Vázquez-Martínez, Andrea; Simó-Algado, Salvador; Amado, Bárbara G. (Acciones e Investigaciones Sociales, 2025)
The comorbidity between depression and alcohol consumption is a public health problem, which can affect the progression and severity of both issues, self-care, treatment adherence, and effectiveness. Moreover, alcohol use in Latin America exceeds the world average. The objectives were a) To study the prevalence of depressive symptomatology and risk alcohol consumption, taking into account gender and age. b) To analyze the relationship between risk alcohol consumption and non-risk alcohol consumption with depressive symptomatology, considering gender and age. A total of 4,890 people aged 18-64 years (mean age = 31.62 years; 62.7% female) from the Dominican Republic, Ecuador, Mexico, Peru, Colombia and Argentina participated. Information was collected using an online questionnaire. The AUDIT-C was used to assess alcohol consumption and PHQ-9 to assess depressive symptoms. Women showed significantly higher risk drinking than men and greater severity of depressive symptomatology. Younger adults (18-24) reported more depressive symptoms. In terms of comorbidity, women with risky alcohol consumption reported greater depressive symptomatology than men; and younger risky alcohol consumers showed greater severity of depressive symptomatology than the other age groups. It is necessary to know what the potential explanatory variables are for the differential results between men and women in risky alcohol consumption and depressive symptomatology, as well as their comorbidity, as this has implications for the design of preventive interventions. Implications for the early management of depression are discussed.